A lesson to learn? A study of how various ranks and police leaders understand and relate to experience-based learning. (21st April 2021) - Hoel, Linda; Barland, Bjørn
ABSTRACT: Improvement through experience-based learning is on the agenda of the Norwegian police. This paper will examine how 'experience-based learning' is understood and practiced by police leaders of different ranks within crisis management. The study's analysis is based on in-depth interviews with Incident Management (IM) police staff members, such as the district chief of police, the chief of IM staff and the control room supervisors. The paper presents three findings. First, the analysis shows there is a difference in the various police ranks in the perception of the term. Second, the police leaders, across the ranks, share an understanding that the police are not sufficiently good at learning and developing practice from experience due to cultural issues within the organisation. Third, there are differences in police leaders' views as to the extent to which closing reports form the basis for changes in practice. The paper discusses the conditions required for experience-based learning as an approach to developing crisis management in the police. The paper argues that improving the police service through experience requires that leaders share a common understanding of the term 'experience-based learning' and its pre-condition such as reflection. The paper suggests that it is necessary for police leaders responsible for EBL to get an opportunity to learn how to learn from EBL, preferably by attending higher education. In this way, the facilitation of EBL can be based on epistemological theory and science.